Microstructure evolution and deuterium trapping in low-energy cascades after irradiation of SS316 stainless steel - Karpov, S.A.; Tolstolutskaya, G.D.; Sungurov, B.S.; Ruzhytskiy, V.V. (Вопросы атомной науки и техники, 2017)
The release profile of deuterium from SS316 austenitic steel irradiated with low-energy deuterium ions was studied using thermal desorption spectroscopy as well as steel microstructure evolution after deuterium implantation and subsequent annealing by means of transmission electron microscopy. It was found that dislocation loops are predominant observed defects in SS316 steel irradiated to dose of ~ 1 dpa. The temperature range of deuterium retention is 300 600 K. Thermal desorption measurements show slightly-resolved stage of deuterium release with a maximum at temperature near 400 K. The energies of deuterium de-trapping have been analyzed using numerical simulations based on diffusion-trapping model. Методом термодесорбційної мас-спектроскопії вивчено термоактивоване виділення дейтерію з аустенітної нержавіючої сталі SS316, опроміненої низькоенергетичними іонами дейтерію, а також досліджено еволюцію мікроструктури сталі після імплантації дейтерію і наступних відпалів за допомогою просвічувальної електронної мікроскопії. Було встановлено, що опромінення до дози ~ 1 зна призводить до утворення дислокаційних петель. Температурний інтервал утримання дейтерію становить 300…600 К. Вимірювання показали наявність однієї слабовирішуваною стадії виходу дейтерію з максимумом при температурі ~ 400 К. Проаналізовано енергії зв'язку дейтерію з пастками по кривим термодесорбції за допомогою чисельного моделювання, заснованого на моделі дифузії атомів газу в полі радіаційних дефектів. Методом термодесорбционной масс-спектроскопии изучено термоактивированное выделение дейтерия из аустенитной нержавеющей стали SS316, облученной низкоэнергетическими ионами дейтерия, а также исследована эволюция микроструктуры стали после имплантации дейтерия и последующих отжигов с помощью просвечивающей электронной микроскопии. Было установлено, что облучение до дозы ~ 1 сна приводит к образованию дислокационных петель. Температурный интервал удержания дейтерия составляет 300…600 К. Измерения показали наличие одной слаборазрешимой стадии выхода дейтерия с максимумом при температуре ~ 400 К. Выполнен анализ энергии связи дейтерия с ловушками по кривым термодесорбции с помощью численного моделирования, основанного на модели диффузии атомов газа в поле радиационных дефектов.